2010
DOI: 10.1177/0193945910381761
|View full text |Cite
|
Sign up to set email alerts
|

What Do Adolescents Think About Teen Parenting?

Abstract: Unexpected increases in the teen birth rates have stimulated a renewed focus on the prevention of teen pregnancy. Although many adults believe there are certain costs associated with teen parenting, the attitudes of teens toward the parenting experience are not known. The purpose of this descriptive study was to determine teens' thoughts on how their lives would change if they experienced a teen birth in the areas of relationships, vocation, and life impacts. The Thoughts on Teen Parenting Survey (TTPS), desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…Stigma was described as precluding young women’s use of contraceptive methods and services. Several other studies have reported similar themes specific to stigma associated with adolescent pregnancy in several countries in sub-Saharan Africa and in the United States (Atuyambe et al, 2005; Hall, Manu, et al, 2015; Herrman & Waterhouse, 2011; Kelly, 1996; Levandowski et al, 2012; Wiemann et al, 2005). …”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Stigma was described as precluding young women’s use of contraceptive methods and services. Several other studies have reported similar themes specific to stigma associated with adolescent pregnancy in several countries in sub-Saharan Africa and in the United States (Atuyambe et al, 2005; Hall, Manu, et al, 2015; Herrman & Waterhouse, 2011; Kelly, 1996; Levandowski et al, 2012; Wiemann et al, 2005). …”
mentioning
confidence: 65%
“…In sexual and reproductive health (SRH), the social, cultural, and religious norms that frame adolescent sexual behavior and its consequences (i.e., pregnancy, early childbearing, abortion, sexually transmitted infections [STIs]) as immoral and problematic may contribute to stigma (Atuyambe, Mirembe, Johansson, Kirumira, & Faxelid, 2005; Fenton, 2010; Fourcroy, 2006; Hall, Kusunoki, et al, 2015; Hall, Manu, et al, 2015; Herrman & Waterhouse, 2011; Kelly, 1996; Kimmel & Garnets, 2003; Levandowski et al, 2012; Luker, 1996; Schalet, 2004; Wiemann, Rickert, Berenson, & Volk, 2005). In turn, SRH stigma may pose barriers to and ultimately prevent the use of family planning, subsequently leading to high rates of unintended pregnancy, unsafe abortion, and maternal mortality among young women in Africa and elsewhere (Hall, Manu, et al, 2015; Hindin, Christiansen, & Ferguson, 2013; Singh, Sedgh, & Hussain, 2010; United Nations Population Fund, 2007; World Health Organization, 2004).…”
mentioning
confidence: 99%
“…As noted in a focus group study of adolescents, young women often become pregnant to ‘have something to love’ 3. An important new realm of research focuses on teens’ attitudes toward the parenting experience and researchers correlated positive attitudes toward a teen birth with an increased risk for subsequent births 4 5. Young women suffering from sexual abuse and neglect, with lives full of stress and anguish, may see the birth of a child as a way to repair complex circumstances, exert power and change in their lives, and create a better future for themselves and their children 6.…”
Section: Commentarymentioning
confidence: 99%
“…One such realm is to determine teens' perceptions of the costs and rewards of early parenting and to base interventions on views of how their lives would change if they had babies as teens (Herrman & Nandakumar, 2012;Herrman & Waterhouse, 2011). Several studies and interventions use this premise, but few are designed for use with a large group in a single session or for this specific setting.…”
Section: Use Of Popular Media In Health Educationmentioning
confidence: 99%
“…The scale yields a cumulative score, subscale scores, and demographic data. (Herrman & Nandakumar, 2012;Herrman & Waterhouse, 2011). Research should also formally evaluate teen and group leader satisfaction with the strategy and methods of implementation.…”
Section: Recommendationsmentioning
confidence: 99%